Factors Influencing Quality of Life in Caregivers of People with Parkinson's Disease and Implications for Clinical Guidelines. (20th December 2012) - Morley, D.; Dummett, S.; Peters, M.; Kelly, L.; Hewitson, P.; Dawson, J.; Fitzpatrick, R.; Jenkinson, C.
Abstract : The quality of life (QoL) of informal caregivers can be adversely affected by a number of factors. This issue, however, has not been well explored for carers of people with Parkinson's (PwP), with research largely restricted to the assessment of caregiver burden and caregiver strain. This study aims to determine the main influences on carer QoL in this population and consider results in the context of current clinical guidelines for the management of Parkinson's disease (PD). Carers completed the newly validated PDQ-Carer, and PwP completed the PDQ-39. The sample comprised 238 carers (mean age 68.20 years) and 238 PwP (mean age 71.64). Results suggest multiple influences on caregiver QoL. These include carer age, gender, health status, and duration of the caregiving role. PwP levels of mobility and cognitive impairment are also significant influences on carer QoL. Not only should practitioners and service providers be particularly aware of the heightened impact of PD on carers over time and as PwP symptoms deteriorate, but this should also be reflected in clinical guidelines for the management of PD.